2019
DOI: 10.1159/000503328
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Asthma-COPD Overlap, Asthma, and Chronic Obstructive Pulmonary Disease Phenotypes in Patients with Airway Obstruction: Influence on Treatment Approach

Abstract: <b><i>Background:</i></b> Many studies have described asthma-COPD overlap (ACO) among patients diagnosed with asthma or chronic obstructive pulmonary disease (COPD), but less so in broad populations of patients with chronic airway obstruction. <b><i>Objective:</i></b> This study aimed to (i) examine the prevalence of ACO, asthma, and COPD phenotypes among subjects referred for pulmonary function testing (PFT), who had airway obstruction in spirometry (forced expi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…COPD is a chronic respiratory disease caused by long-term exposure to toxic particles or harmful gases that leads to pathological changes throughout the respiratory system, including the airways, lung parenchyma, pulmonary alveolar, and pulmonary vasculature [ 5 ]. A clinical survey in China has shown [ 14 , 15 ] that COPD is prevalent in people over 40 years old, and the disease may rank 3rd for fatal diseases and 5th for the economic burden of diseases in the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD is a chronic respiratory disease caused by long-term exposure to toxic particles or harmful gases that leads to pathological changes throughout the respiratory system, including the airways, lung parenchyma, pulmonary alveolar, and pulmonary vasculature [ 5 ]. A clinical survey in China has shown [ 14 , 15 ] that COPD is prevalent in people over 40 years old, and the disease may rank 3rd for fatal diseases and 5th for the economic burden of diseases in the world.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, much attention has been paid to respiratory training, which has achieved the goal of improving lung function of patients through exercises such as glottic vocalization training and breathing exercise. Some scholars believe [ 5 ] that performing respiratory training for COPD patients is able to effectively improve their respiratory function, thus resulting in improved pulmonary function, and this training modality has been demonstrated in patients with cancer complicated by stroke, stroke hemiparesis, and chronic rotator cuff injury [ 6 8 ]. Western medicine can effectively improve many discomfort symptoms in patients, and it plays an important role in anti-inflammation and improving diaphragm function.…”
Section: Introductionmentioning
confidence: 99%
“…These biomarkers can assist clinicians to accurately identify patients, thereby to maximize the effects of the personalized treatment ( 11 ). There are extremely differences in evidence-based treatment between asthma and COPD: because frequent use of ICS can increase the risk of pneumonia ( 44 ), it is recommended to use long-acting β 2 -agonist (LABA) and/or long-acting muscarinic antagonists (LAMA) alone (without ICS) as the initial treatment for COPD; but contraindicated for asthma and ACO due to the risk of serious deterioration and death ( 45 ). In addition, because the prognosis of patients with ACO is significantly worse, some guidelines recommend add-on therapy of LAMA to the basis treatment of ICS and LABA (i.e., triple therapy) ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, group A had lower levels of serum inflammatory factors than group B after treatment. Romem et al [18] demonstrated in an animal study that montelukast inhibited the release of IL-6 in sensitized asthmatic rats and reduced the accumulation of bronchial inflammatory cells in asthmatic rats, which relieved airway inflammation and prevented airway immune damage. It indicates that montelukast may inhibit the inflammatory response of patients with pulmonary or bronchial diseases and alleviate clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%